2020
DOI: 10.1073/pnas.2004809117
|View full text |Cite
|
Sign up to set email alerts
|

KSHV LANA acetylation-selective acidic domain reader sequence mediates virus persistence

Abstract: Viruses modulate biochemical cellular pathways to permit infection. A recently described mechanism mediates selective protein interactions between acidic domain readers and unacetylated, lysine-rich regions, opposite of bromodomain function. Kaposi’s sarcoma (KS)-associated herpesvirus (KSHV) is tightly linked with KS, primary effusion lymphoma, and multicentric Castleman’s disease. KSHV latently infects cells, and its genome persists as a multicopy, extrachromosomal episome. During latency, KSHV expresses a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Functional motifs and empirically determined domains of LANA were annotated. These include the Histone 2A/B binding domain (the chromosome binding motif), nuclear localization signals (NLS) [ 32 34 ], the SUMO-interacting motif (SIM) [ 33 , 35 ], the Elongin B and C box (BC-box) [ 33 , 36 ], and the proline- and the aspartic-glutamic acid-rich regions within the N-terminal region, along with the glutamine-glutamic acid-rich region and the Cullin 5 box (Cul-Box) within the DNA binding domain (DBD) on the C-terminus [ 33 , 36 ]. Finally, results from a B-cell epitope predictor were included using default parameters (BepiPred-2.0) [ 14 ], where the epitope prediction scores are represented in probabilities mapped on the alignments as a heatmap.…”
Section: Methodsmentioning
confidence: 99%
“…Functional motifs and empirically determined domains of LANA were annotated. These include the Histone 2A/B binding domain (the chromosome binding motif), nuclear localization signals (NLS) [ 32 34 ], the SUMO-interacting motif (SIM) [ 33 , 35 ], the Elongin B and C box (BC-box) [ 33 , 36 ], and the proline- and the aspartic-glutamic acid-rich regions within the N-terminal region, along with the glutamine-glutamic acid-rich region and the Cullin 5 box (Cul-Box) within the DNA binding domain (DBD) on the C-terminus [ 33 , 36 ]. Finally, results from a B-cell epitope predictor were included using default parameters (BepiPred-2.0) [ 14 ], where the epitope prediction scores are represented in probabilities mapped on the alignments as a heatmap.…”
Section: Methodsmentioning
confidence: 99%
“…mLANA also carries an E3 ligase domain essential for GC B cell expansion (54). Conservation between mLANA and kLANA facilitated studies examining precise domains of kLANA crucial for in vivo function (55)(56)(57) and revealed that kLANA and mLANA are functionally interchangeable for episome maintenance (58,59).…”
Section: Mhv68 Latency-associated Nuclear Antigenmentioning
confidence: 99%
“…Intriguingly, the same recognition of unacetylated p53 by the acidic domain reader has been further demonstrated during the virus infection process. Latency-associated nuclear antigen, which is encoded by Kaposi’s sarcoma (KS)-associated herpesvirus (KSHV) and contains two tandem acidic domains, selectively interacts with unacetylated p53 and facilitates KSHV latency establishment ( Juillard et al, 2020 ).…”
Section: The Ptm Code and Its Functional Readout For P53mentioning
confidence: 99%